2018
DOI: 10.3892/etm.2018.6676
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of photodynamic therapy combined with imiquimod in the treatment of anal condyloma acuminatum and its effect on immune function

Abstract: Therapeutic effect of photodynamic therapy combined with imiquimod in the treatment of anal condyloma acuminatum (CA) was investigated to explore its effect on immune function. A total of 104 patients with anal CA were randomly divided into two groups: Patients in the study group were treated with photodynamic therapy combined with imiquimod, and ii) patients in the control group were treated with recombinant human interferon α-2b cream. Clinical efficacy and immune function related indicators were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our study demonstrated that thymosin combined with photodynamic therapy effectively reduced the number and area of CA in the anal canal and reduced the adverse reactions caused by drugs, while the tingling, redness, and swelling occurred during the treatment. Related research results show that LTN, SP, and other immune factors are closely related to the occurrence, development, and recurrence of CA [24]. LTN can effectively attract leukocytes to gather in the infected site and participate in the regulation of immune function by activating natural killer cells, T cells, and enhancing mucosal immunity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our study demonstrated that thymosin combined with photodynamic therapy effectively reduced the number and area of CA in the anal canal and reduced the adverse reactions caused by drugs, while the tingling, redness, and swelling occurred during the treatment. Related research results show that LTN, SP, and other immune factors are closely related to the occurrence, development, and recurrence of CA [24]. LTN can effectively attract leukocytes to gather in the infected site and participate in the regulation of immune function by activating natural killer cells, T cells, and enhancing mucosal immunity.…”
Section: Discussionmentioning
confidence: 97%
“…Related research results show that LTN, SP, and other immune factors are closely related to the occurrence, development, and recurrence of CA [ 24 ]. LTN can effectively attract leukocytes to gather in the infected site and participate in the regulation of immune function by activating natural killer cells, T cells, and enhancing mucosal immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No glottic synechia was observed following treatment in our cases. In addition to the above-described mechanism of action, ALA-PDT increases CD4+, CD4+/CD8+ and IFN-γ, and reduces CD8+, IL-4, and IL-10 in HPV-infected cells, which may also contribute to the curing of intractable laryngeal papillomatosis ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that the major cause of COPD is immune function disorder that increases the risk of inflammation [13,14]. Immune function is the key to COPD treatment, and T lymphocytes can directly reflect the body's immune function status [53]. e spleen is the Evidence-Based Complementary and Alternative Medicine largest immune organ in the body and contains a large number of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%